2020
DOI: 10.1111/desc.13032
|View full text |Cite
|
Sign up to set email alerts
|

Infant Spontaneous Motor Tempo

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
2
28
2
Order By: Relevance
“…Whilst in this case SMS was measured using Motion Capture, which requires specialist equipment, the same analyses can be applied to 2D video data using AI technology, or even by measuring the sound signal produced by the drumming infant (e.g. Rocha et al, 2021). The current data can therefore provide distinct added value to neural measures in finding behavioural markers that are suitable for large scale, low cost, screening for intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst in this case SMS was measured using Motion Capture, which requires specialist equipment, the same analyses can be applied to 2D video data using AI technology, or even by measuring the sound signal produced by the drumming infant (e.g. Rocha et al, 2021). The current data can therefore provide distinct added value to neural measures in finding behavioural markers that are suitable for large scale, low cost, screening for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Infant SMT, as measured via a free drumming task, becomes faster and less variable with age, presumably in line with development of motor control (Rocha, Southgate & Mareschal, 2021). Rocha et al (2021) reported an SMT of drumming close to 2 Hz (542 ms Inter-Onset-Interval; IOI) for infants with a mean age of 11 months.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Investigation of the ontogeny of rhythmic movement may offer unique insights into the origins of this bidirectional relationship. While the ability to synchronize one's movement to music develops slowly across childhood (see [5]), infants from five months of age can produce a spontaneous motor tempo (SMT, or natural rate of rhythmic movement) [6]. The current paper asks if the link between auditory and gross motor rhythm can be in part explained by the prevalent behaviour of infant carrying.…”
Section: Introductionmentioning
confidence: 96%
“…In a cross-sectional study of infant drumming over the first years of life, Rocha et al [6] found that infant SMT was predicted by parental body size, but not infant's own body size. Specifically, parent height predicted infant SMT such that infants with taller parents showed a slower SMT than infants with shorter parents.…”
Section: Introductionmentioning
confidence: 99%